Frequency and Correlation of Hypogonadism in Men with Type 2 Diabetes - Adnan Ali, Afaq Naeem, Laiba Naseer, Nadeem Naeem, Shahid Waheed, Maryam Mastoor (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The present study aimed to determine the frequency and association of hypogonadism in men with type 2 diabetes mellitus. Material and Methods: This cross-sectional study was conducted on 242 type 2 DM male patients in the Department of General Medicine, Bahria International Hospital, Lahore from 16th January 2022 to 15th July 2022. The Androgen deficiency in aging male (ADAM) questionnaire was used for screening hypogonadal symptoms in the study group. The presence of low serum testosterone below 3 ng/mL and positive ADAM score was referred to as hypogonadism. T2DM patients with and without hypogonadism had their clinical and biochemical variables compared. Total testosterone, BMI, free testosterone, waist circumference, and sex hormone–binding globulin were measured. SPSS version 26 was used for data analysis. Results: Of the total 242 T2DM male patients, the prevalence of hypogonadism was 24.8% (n=60). The most prevalent symptoms in T2DM patients were hypogonadal symptoms. The overall mean age was 45.8± 9.63 years with range (25-70 years). Mean BMI value was 24.8 ± 3.64 kg/m2. The incidence of overweight and obese patients were 17.8% and 49.3% respectively. The prevalence of erectile dysfunction, reduced libido, and work performance deterioration in hypogonadism were 94.8%, 68.2%, and 56.3% respectively. T2DM patients without hypogonadism had lower a) incidence of diabetic neuropathy (18.6% vs. 43.8%; p=0.021), b) T2DM duration (5.3± 3.82 vs. 9.2± 4.9 years; P=0.002), c) occurrence of diabetic retinopathy (26.9% vs. 57.8%; P=0.006), and d) HbA1c (8.9± 1.53% vs. 9.9 ± 2.54%: P=0.005), and insulin therapy (21.5% vs. 45.8%: P=0.031) compared to those with hypogonadism. Conclusion: The present study found that prevalence of hypogonadism was 24.8% in type 2 diabetes mellitus. Patients with hypogonadism had higher HbA1c, higher prevalence of neuropathy and retinopathy, longer diabetic duration, and predominantly used insulin therapy than those T2DM patients without hypogonadism. Keywords: Hypogonadism, Type 2 diabetes mellitus, Androgen deficiency in aging male (ADAM).